Normative Studies of Restorative Justice As A Form of Fulfillment of The Rights Of Crime Victims In The Indonesian Criminal Justice System - Nurhaqi, Ari (Ann Publisher, 2025)
Background: Everyone has the potential to commit crimes, which means violating human rights. With this restriction, which affects us as human beings, given that others are suspected of violating human rights, it is a must. Aim, such an attitude has not been seen when someone sees a police officer who is suspected of violating human rights. Methods and literature review used in this paper Results, In police institutions, there are policies such as Discretion, Community Policing (Polmas), Alternative Dispute Resolution (ADR), and Restorative Justice, which include victims in their implementation. The existence of this policy affects the settlement of criminal acts by the police. Conclusions. The existence of this policy affects the police's settlement of criminal acts.